(untitled) (Research, Society and Development, 2020)
The objective of the research is to identify the municipal socioeconomic factors that determine access to higher education. The binary logit model was used econometric. The dependent variable accommodated two categorical dummy 1 responses if access to higher education and dummy 0 otherwise. The independent variables considered were: illiteracy, unemployment, education, GDP per capita, household income, health and IFDM. Data analysis was performed using the Eviews statistical package at a significance level of 5%. As a result, it was found that of the variables under study, only the illiteracy variable was not statistically significant. The variables, unemployment, household income and IFDM were positive and statistically significant, which means they had a direct relationship. The variables PIB per capita, education and health had a negative sign (the unexpected priore) and statistically significant, presented an inverse relation with the dependent variable. To a certain extent, all variables in practice may have a strong influence on whether or not people have access to higher education, although some have had a negative relationship.